2016
DOI: 10.1128/aem.02447-16
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bartonella Species with Wild and Synanthropic Rodents in Different Brazilian Biomes

Abstract: Bartonella spp. comprise an ecologically successful group of microorganisms that infect erythrocytes and have adapted to different hosts, which include a wide range of mammals, besides humans. Rodents are reservoirs of about two-thirds of Bartonella spp. described to date; and some of them have been implicated as causative agents of human diseases. In our study, we performed molecular and phylogenetic analyses of Bartonella spp. infecting wild rodents from five different Brazilian biomes. In order to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 58 publications
7
45
0
2
Order By: Relevance
“…Though these rats can disperse over long distances, investigations of marked animals demonstrated that they tend to live within small individual territories, sometimes not extending beyond a single building. Genetic analysis using microsatellite markers showed that rats demonstrate strong site fidelity (Gardner-Santana et al, 2009). However, there was evidence of infrequent, longdistance movements within the city indicated by capturing some rats 2-11.5 km away from the locations assigned based on the genetic analysis (Gardner-Santana et al, 2009).…”
Section: Ecology Of Rats In Urban Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though these rats can disperse over long distances, investigations of marked animals demonstrated that they tend to live within small individual territories, sometimes not extending beyond a single building. Genetic analysis using microsatellite markers showed that rats demonstrate strong site fidelity (Gardner-Santana et al, 2009). However, there was evidence of infrequent, longdistance movements within the city indicated by capturing some rats 2-11.5 km away from the locations assigned based on the genetic analysis (Gardner-Santana et al, 2009).…”
Section: Ecology Of Rats In Urban Settingsmentioning
confidence: 99%
“…Genetic analysis using microsatellite markers showed that rats demonstrate strong site fidelity (Gardner-Santana et al, 2009). However, there was evidence of infrequent, longdistance movements within the city indicated by capturing some rats 2-11.5 km away from the locations assigned based on the genetic analysis (Gardner-Santana et al, 2009). Among factors influencing rat presence and abundance, Himsworth et al (2014b) suggested building condition and specific land use.…”
Section: Ecology Of Rats In Urban Settingsmentioning
confidence: 99%
“…have been detected in a variety of wild animals all over the world. In Brazil, these agents have been reported in several wild mammals, such as wild carnivores [15][16][17], deer [18], peccary [19], non-human primates [20,21], and rodents [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Different species of Bartonella associated with rodents have been implicated as causing human disease, including endocarditis, myocarditis, fever, neurological signs, meningitis, splenomegaly and lymphadenopathy (Buffet et al, 2013;Gutiérrez et al, 2015;Gonçalves et al, 2016). Studies from Argentina are rare, with only Bartonella henselae and Bartonella quintana in humans, B. henselae and Bartonella vinsonii subsp.…”
mentioning
confidence: 99%